Interview as a communicative approach in foreign language teaching (in secondary schools) - Irina G. Bakanova; Kate A. Patrikeyeva; Nataliya A. Pyrkina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article focuses on the forms and contents of an interview for secondary school learners of a foreign language. Special attention is given to the advantages of using an interview for developing learners’ communication skills. A system approach to defining the term "interview" brings us to the conclusion that there is a certain structure of interacting components. The presented classifications of types (organizational forms) of interviews make it possible for teachers to choose a specific type of an interview based both on the educational goals and objectives as well as on the process of conducting an interview. The content of foreign language teaching is based on an integrated approach and a didactic principle of learning in a language environment. The approach is targeted at studying a foreign language for practical purposes in a positive emotional environment. Therefore, an interview enables the trainees to carry out efficient interaction in a specific communicative situation as the learning process becomes a sample communication process. At the same time the article focuses on the fact that efficient interviewing at foreign language lessons in a secondary school depends on the careful preparation both by the teacher and students.